A fluid mechanics approach to evaluating marine soft clay strength by a ball full-flow penetrometer. (November 2021) - Guo, Xingsen; Nian, Tingkai; Gu, Zhongde
Highlights: The CFD approach is used to analyze the interaction between the ball and marine soft clays described by non-Newtonian fluids with shear thinning characteristics and rate effect. The fluid solutions of the bearing capacity factor N and the equations of N considering different rate effect parameter λ at rough and smooth ball surface conditions are given. The influence of the rate effect parameter, density and strength of the marine soft clay on N are systematically analyzed during the ball's deep penetration. The stress state of the marine soft clays around the ball and the mechanism of the rate effect leading to the variation of N are elucidated in detail. Abstract: Ball full-flow penetrometer is widely used for testing the ultimate bearing pressure q of marine soil to evaluate the undrained shear strength s u by the proposed bearing capacity factor N, and thus N is one of the primary concerns of marine geotechnical engineers. However, plastic constitutive model solutions of N resolved by using classical rigid-plastic materials described by the Tresca yield criterion are not suitable for evaluating the low-strength marine soft clays with viscous fluid characteristics. In this paper, the validated computational fluid dynamics (CFD) approach is used to simulate the interaction between the ball with smooth and rough surfaces and marine soft clays described by non-Newtonian fluids with shear thinning characteristics and rate effect. Based on this, the effects of the rate effect parameter λ, density and strength of the marine soft clay on N are systematically analyzed. Furthermore, during the ball's deep penetration, the equations of N considering different λ at rough and smooth ball surface conditions are established. Finally, the stress state of the marine soft clays around the ball and the mechanism of the rate effect leading to the variation of N are elucidated by the pressure distribution contours on the ball surface, the shear rate contours of the marine soft clay on the ball surface, and the velocity field contours of the marine soft clay around the ball, which provides a basis for the undrained shear strength s u evaluation of low-strength marine soft clays.